2019
DOI: 10.1007/s40279-019-01101-0
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Exercise: What Next?

Abstract: Caffeine is a widely utilized performance-enhancing supplement used by athletes and non-athletes alike. In recent years, a number of meta-analyses have demonstrated that caffeine’s ergogenic effects on exercise performance are well-established and well-replicated, appearing consistent across a broad range of exercise modalities. As such, it is clear that caffeine is an ergogenic aid—but can we further explore the context of this ergogenic aid in order to better inform practice? We propose that future research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 212 publications
(248 reference statements)
1
115
0
12
Order By: Relevance
“…Future studies are needed to explore optimal doses of caffeine and sodium bicarbonate that have the largest effect on performance while producing the least sideeffects. 48 In addition to doses, future work is need on the optimal timing of ingestion. Timing of ingestion may be especially important to investigate when it comes to sodium bicarbonate given that there is very large inter-individual variability in responses to sodium bicarbonate ingestion, 9,39,40 and the timing of ingestion is also affected by the mode of delivery.…”
Section: Figmentioning
confidence: 99%
“…Future studies are needed to explore optimal doses of caffeine and sodium bicarbonate that have the largest effect on performance while producing the least sideeffects. 48 In addition to doses, future work is need on the optimal timing of ingestion. Timing of ingestion may be especially important to investigate when it comes to sodium bicarbonate given that there is very large inter-individual variability in responses to sodium bicarbonate ingestion, 9,39,40 and the timing of ingestion is also affected by the mode of delivery.…”
Section: Figmentioning
confidence: 99%
“…Studies that have reported individual participant data suggest that some individuals experience an increase in performance following caffeine ingestion, whereas others do not [4][5][6]. In order to develop more effective guidelines for caffeine supplementation in sport and exercise settings, the scientific focus has recently been placed on examining and understanding the reasons for the between-individual variation in responses [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, individuals with the AA genotype are commonly classified as "fast caffeine metabolizers", whereas C allele carriers (AC/CC genotypes) are considered to be "slow caffeine metabolizers", respectively [13]. The influence of CYP1A2 (rs762551) on the acute effects of caffeine supplementation on exercise performance has been explored in several studies [14][15][16][17][18][19][20][21][22][23]. However, the evidence in these studies remains inconsistent, with some reporting no effect of the polymorphism on the ergogenic effects of caffeine supplementation and others showing a modifying effect, but in different directions [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%